Novel Path to Activation of Vascular Smooth Muscle Cells: Up-Regulation of gp130 Creates an Autocrine Activation Loop by IL-6 and Its Soluble Receptor - Mariam Klouche; Sucharit Bhakdi; Monika Hemmes; Stefan Rose‐John (1999)
Abstract This study describes a novel path to the activation of smooth muscle cells (SMC) by the IL-6/soluble IL-6 receptor (sIL-6R) system. Human vascular SMC constitutively express only scant amounts of IL-6R and so do not respond to stimulation with this cytokine. We show that SMC also do not constitutively express appreciable levels of gp130, which would render them sensitive to transsignaling by the IL-6/sIL-6R complex. Because gp130 is generally believed not to be subject to regulation, SMC would thus appear not to qualify as targets for the IL-6/sIL-6R system. However, we report that treatment of SMC with IL-6/sIL-6R provokes marked up-regulation of gp130 mRNA and surface protein expression. This is accompanied by secretion of IL-6 by the cells, so that an autocrine stimulation loop is created. In the wake of this self-sustaining system, there is a selective induction and secretion of MCP-1, up-regulation of ICAM-1, and marked cell proliferation. The study identifies SMC as the first example of cells in which gp130 expression is subject to substantive up-regulation, and discovers a novel amplification loop involving IL-6 and its soluble receptor that drives SMC into a proinflammatory state.